Role Factors That Affecting Non Exclusive Breastfeeding (Qualitative Study At Pegandan Health Center) (Public Health Perspective Journal, 2020)
Exclusive breastfeeding decreases with age. Based on data in Semarang City, Pegandan Health Center is the second consecutive year (2016-2017) in the lowest exclusive breastfeeding (24.69%). This shows that there are still many mothers who give non-exclusive breastfeeding. The problem in this study is what factors cause non-exclusive breastfeeding. The purpose of this study was to obtain an overview of the causes of non-exclusive breastfeeding by mothers in area of Pegandan Health Center. The research is a descriptive study with a qualitative approach. The informants in this study were mothers who had babies aged 0-12 months and obtained as many as 12 informants. The data collection technique was done by in-depth interviews using interview guidelines. The results found that low knowledge, lack of motivation, lack of husband and family support made mothers fail to provide exclusive breastfeeding. Suggestions for health center are to increase counseling about exclusive breastfeeding, not only mothers, but also those closest to them such as grandmothers / husbands that can be done through routine meetings such as PKK or other routine meeting activities.